Formation of syndromes of war and their features - Danyk, Yuriy; Druz, Oleg; Chernenko, Inna (Journal of Education, Health and Sport, 2016)
With the use of content analysis of modern theoretical and empirical studies, the factors of wars syndrome formation are analyzed. It has been established that under the influence of stress factors and other factors of wars (military conflicts) on their participants, there are both common and specific features of manifestations of known syndromes of wars (Vietnamese, Chechen, Afghan, Persian Gulf syndrome, etc.). It is proved that, by common signs, all syndromes of wars can be combined into a single basic category - war syndrome with separation of specific wars into specific war syndromes according to the place where they occurred, under the influence of which factors they formed and the manifestations of which they are characterized. The authors provided the classification of syndromes of wars. Definitions are formulated and the syndrome of wars and «hybrid war syndrome» are described. Some of the most significant features of the «hybrid war syndrome» are described. It has been established that during the formation of the «hybrid war syndrome», the place and time of a crisis situation acquire their own characteristics depending on where conventional or non-conventional actions are conducted, with the predominant role of informational, psychological, cognitive actions and cognitive subjective changes among their participants.